2005
DOI: 10.1001/archopht.123.10.1422
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in the GJA1 Gene in a Family With Oculodentodigital Dysplasia

Abstract: Objectives: To describe a Brazilian family with oculodentodigital dysplasia (ODDD) and to screen for mutations in the gap junction protein alpha 1 (GJA1) gene in this family.Methods: Twelve members of a 3-generation family with ODDD underwent screening for mutations of the GJA1 gene and a comprehensive ophthalmic examination. We defined ODDD on the basis of clinical characteristics described in this syndrome (microdontia, caries, enamel hypoplasia, thin nose,andsyndactyly)andeyeabnormalitiessuchasmicrophthalmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…These mice carry a G60S amino acid substitution in the first extracellular loop of Cx43, one residue removed from the P59H mutation identified in some human ODDD patients [20]. Consistent with in vitro studies, Cx43…”
Section: Introductionsupporting
confidence: 63%
“…These mice carry a G60S amino acid substitution in the first extracellular loop of Cx43, one residue removed from the P59H mutation identified in some human ODDD patients [20]. Consistent with in vitro studies, Cx43…”
Section: Introductionsupporting
confidence: 63%
“…Jrt allele) in the first extracellular loop of Cx43, which is one residue away from the P59H mutation identified in human ODDD patients (Vasconcellos et al, 2005). Our previous work demonstrated that the granulosa cells isolated from these mice (Gja1 Jrt /+) exhibit either very weak coupling (10-20% versus wild type) or a complete lack of coupling, indicating that the G60S mutant dominantly inhibits the function of co-expressed wild-type Cx43 in vivo (Flenniken et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…eye disorders (Debeer et al, 2005) including glaucoma (Vasconcellos et al, 2005) [see also Table 3 of Loddenkemper et al (Loddenkemper et al, 2002)]. A mouse model of ODDD with a G60S mutation in Cx43 also shows eye abnormalities (Flenniken et al, 2005).…”
Section: Oddd Patients With Different Cx43 Mutations Show Variablementioning
confidence: 99%